Pseudo-one-dimensional nucleation in dilute polymer solutions - Zhang, Lingyun; Schmit, Jeremy D. (My University, 2016)
Pathogenic protein fibrils have been shown in vitro to have nucleation-dependent kinetics despite the fact that one-dimensional structures do not have the size-dependent surface energy responsible for the lag time in classical theory. We present a theory showing that the conformational entropy of the peptide chains creates a free-energy barrier that is analogous to the translational entropy barrier in higher dimensions. We find that the dynamics of polymer rearrangement make it very unlikely for nucleation to succeed along the lowest free-energy trajectory, meaning that most of the nucleation flux avoids the free-energy saddle point. We use these results to construct a three-dimensional model for amyloid nucleation that accounts for conformational entropy, backbone H bonds, and side-chain interactions to compute nucleation rates as a function of concentration.
Citation: Zhang, L. Y., & Schmit, J. D. (2016). Pseudo-one-dimensional nucleation in dilute polymer solutions. Physical Review E, 93(6), 6. doi:10.1103/PhysRevE.93.060401
Keywords: Solid-State Nmr; Alzheimers-Disease; Amyloid Formation; Fibrils; Mechanism; Kinetics